2010
DOI: 10.1007/s10152-010-0231-2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of fish larvae in the northern Ionian Sea (Eastern Mediterranean)

Abstract: The purpose of this paper was to study the spatial distribution, abundance and composition of fish larvae in the northern Ionian Sea. Samples were collected to the 600 m depth with an electronic multinet BIONESS during the ''INTERREG Italia-Grecia'' oceanographic cruise carried out in March 2000 off the Apulian Italian coast. A total of 46 species of teleost early stages were collected, belonging to 38 genera and 22 families. Over 52% of the larvae identified were mesopelagic species, almost 27% were demersal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
4
13
0
Order By: Relevance
“…The presence of the mesopelagic larvae in the upper layer was also reported by other previous studies in the northwestern Mediterranean (Olivar et al, 2010;Granata et al, 2011;Torres et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…The presence of the mesopelagic larvae in the upper layer was also reported by other previous studies in the northwestern Mediterranean (Olivar et al, 2010;Granata et al, 2011;Torres et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…This case study evidenced the need to assess specific environmental conditions driving the Giordano et al, 2014;Granata et al 2011;Sabatés & Olivar, 1996) but with mesoscale oceanographic structures (e.g. surface currents, gyres and fronts), as reported in different cases by Bakun (2006), Basilone et al (2013), Palomera (1992) and Sabatés et al (2001).…”
Section: Discussionmentioning
confidence: 96%
“…Extensive work has mainly covered the coastal waters of the north-western part of the Mediterranean Sea (Alemany et al, 2006;Alvarez et al, 2012;García & Palomera, 1996;Olivar et al, 2012;Olivar & Sabatés, 1997;Palomera & Olivar, 1996;Palomera & Sabatés, 1990;Sabatés, 1990Sabatés, , 2004Sabatés & Olivar, 1996;Sabatés et al, 2007) and to a lesser extent the central (Cuttitta et al, 2003(Cuttitta et al, , 2004 and the eastern parts (Aegean Sea: Isari et al, 2008;Somarakis et al, 2011;Tsikliras & Koutrakis, 2011;Tsikliras et al, 2014; eastern Ionian waters: Granata et al, 2011;Tunisian waters: Koched et al, 2013;Zarrad et al, 2013). These studies carried out in the Mediterranean Sea showed that there was a clear bathymetric separation of larval fish assemblages, due to different spawning behavior of adults: inshore assemblages have a different composition from offshore ones (Alemany et al, 2006;Giordano et al, 2014;Granata et al 2011;Sabatés & Olivar, 1996). Generally, bathy and mesopelagic families were characteristic members of the oceanic group, while the inshore species consist of pelagic and demersal (Beldade et al, 2006;Sabatés et al, 2003;Tsikliras & Koutrakis, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Larval fish assemblages are temporary components (meroplankton) of the zooplankton community, the structure of which is ultimately dependent upon reproductive cycles within populations of adult fish (Antonia et al 2010, Hasan et al 2003, Lanksbury et al 2005. Ichthyoplankton studies are an important tool for providing information for ichthyology, environmental inventory, stock monitoring, and fisheries management (Rogério et al 2010).…”
Section: Introductionmentioning
confidence: 99%